(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2024)
Introduction: Autism Spectrum Disorders (ASD) are increasing alarmingly in recent times making it an important emerging public health problem. The role of parents is of paramount importance in meeting the educational needs of their special children with ASD. Objectives: To find out the role of parents in meeting the educational needs for their children with ASD. Methods: This descriptive type of cross sectional study was carried out among the 61 purposively selected respondents who were attended to Center for Neurodevelopment and Autism in Children, BSMMU, Dhaka and Proyash School, Dhaka cantonment, Dhaka. The data were collected through face to face interview by semi structure questionnaire. Results: This study revealed that the mean age of the children was 6.65 years with SD±2.763 years, 72.1% children with autism were male and 27.9% of them were female. In this study, maximum 39.3% of mothers were HSC qualified and 50.8% of fathers were graduated, 80% mothers were housewife and 20% were in service. It was found that among the children about 52.5% were detected abnormality within first 18 months of age and about 47.5% were detected after 18 months of age. The association between age of first abnormality detection and mother’s educational level was statistically significant (p=.025). The present study also reveals that 82% of mother had knowledge about autism, 88.5% of them feels that their children need special education for taking care. It was found in the study about 70.5% mother spent more than 4 hours time/day for taking care of their children at home whereas 29.5% of them spent 1-4 hours of time/day and detection of abnormality of the children was delayed among less educated mothers in comparison to educated mothers. Conclusion: All this findings suggests that parent’s educational needs for taking care of their children with ASD. In this aspect in-depth study on broader perspective is needed for more accurate description of the problem. JAFMC Bangladesh. Vol 19, No 1 (June) 2023: 42-46